2014
DOI: 10.1007/s00128-014-1258-x
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Trace Element Levels in Milk and Blood of Buffaloes (Bubalus bubalis) from Hyderabad, India

Abstract: The presence of lead (Pb) in milk and its interaction with trace elements is a serious health concern. Present study is aimed at determining Pb and trace element (Fe, Zn and Mg) levels in milk and blood/serum samples of lactating buffaloes (Bubalus bubalis) living in a market-area (Group-A) and a dairy-experimental station (Group-B), Hyderabad, India. In addition, kidney and liver function tests were assessed. Fodder, milk and blood Pb levels were significantly (p < 0.01) higher in Group-B. Elevated Pb levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Additionally, the concentrations of most elements in goat milk were higher than those in cow milk (Table 4), as previously reported [27][28][29]. In the present study, Zn concentration in buffalo milk was five times higher than that in buffalo milk from India, while Fe concentrations were similar between the two studies [30].…”
Section: Concentrations Of Trace Elements In Milk Samplessupporting
confidence: 88%
“…Additionally, the concentrations of most elements in goat milk were higher than those in cow milk (Table 4), as previously reported [27][28][29]. In the present study, Zn concentration in buffalo milk was five times higher than that in buffalo milk from India, while Fe concentrations were similar between the two studies [30].…”
Section: Concentrations Of Trace Elements In Milk Samplessupporting
confidence: 88%
“…However, based on the standard deviation observed in this study, we can suggest a higher heterogeneity of milk heavy metal contamination within areas than between areas. This was expected as the contamination of milk by heavy metals is mainly due to contamination of the environment and also the contamination of fodder given to the dairy cows (Mohajeri et al, 2014;Shailaja et al, 2014). For instance, the proximity of lead zinc factories favoured contamination (Mohajeri et al, 2014;Patra et al, 2008;Swarup et al, 2005).…”
Section: Pb (μG/l)mentioning
confidence: 95%
“…For instance, calcium, copper, and selenium are essential minerals for normal human body functions, as they are involved in many physiological processes (Alasalvara et al, 2002;Licata et al, 2012). However, heavy metals such as lead (Pb), arsenic (As), and cadmium (Cd) may also be found in milk (Swarup et al, 2005;Shailaja et al, 2014). If they are consumed in excessive concentrations, these heavy metals can lead to serious systemic health problems (Oliver, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation in livestock : A study in 2014 showed about 2.5 times higher Pb in blood and milk samples of lactating buffalos housed in university facility as compared to buffaloes from local shandies13. An inverse correlation between BLL with serum elements (Fe, Zn and Mg) and positive association with creatinine, alanine aminotransferase and ALP was also recorded.…”
Section: Investigational Reportsmentioning
confidence: 99%